DETERMINAN KESIAPAN MENIKAH PADA REMAJA AKHIR DI WILAYAH KERJA KUA TERNATE SELATAN - Istiana Asrari Bansu; Siti Hubaya Matjiono (Politeknik Kesehatan Kementerian Kesehatan Kalimantan Timur, 2020)
According to the Child Protection Law, the appropriate age for female and male to get married are 21 and 25 years old respectively. Age under 18 is not considered as an adult. Junior Clerk and Legal Division of the National Religious Court Class I B in Ternate published that couples in their 20’s is the biggest contributor of the filled divorce cases and among them, the wives dominate as the plaintiff. This study is to analyze the influential variables to the attentiveness in marriage in their late adolescence/ early adulthood. Quantitative approach was used in this study using cross sectional method. The subject of the assessment are couples that already have submitted for their marriage planning in KUA South Ternate working area. Total of 80 respondents are evaluated using total sampling technique. Chi-square and logistic regression techniques are employed to determine the impactful variables to the attentiveness in marriage. The result of the chi-square test shows that attitude, knowledge, and parenting pattern are the most meaningful variables with p-value of 0.008, 0.000, and 0.020 respectively. On the other side, the logistic regression result tells us that the positive or supportive attitude increases the probability to get married by 6.8 times, while the rich of knowledge will rise it by 2.8 times and 4.3 times for the positive influence of acquittances.